(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mulyana AN, Proyambodo S, Triwidodo H, Hendarjanti H, Sahari B. 2020. An assessment of the reproduction, predation, and nesting behavior of Sulawesi Masked-owl (Tyto rosenbergii) in oil palm plantation: A case study of West and Central Sulawesi, Indonesia. Biodiversitas 21: 5685-5689. The quality and quantity of yield in palm plantations are reduced due to inevitable factors such as pests, diseases, and weeds. Furthermore, owls (Tytonidae) play a role as potential predators to control rats, the major pest. Therefore, this study aims to observe the reproduction patterns, predation, and nesting behavior of Tyto rosenbergii. To achieve this, direct observation and the installation of a camera trap in the nest box was adopted. Furthermore, a predation test was carried out by feeding the owls with rats daily in a cage measuring 4m x 8m x 6m. The results showed that the number of eggs produced ranged from 2 to 6, with an average of 3.85. Also, the Percentage of hatching ranges between 0-100% with an average of 80.77%, and that of chicks that survive to the fully feathered is 51%. In addition, T. rosenbergii was able to prey on 1-4 rats per night, and its activity mostly occurs outside the cage than inside, except when they had a reproductive season.